Case Studies of Challenges in Emergency Care for Children With Autism Spectrum Disorder. Issue 12 (20th December 2021) - Gray, James M.; Roback, Mark G.
Abstract: Autism spectrum disorder (ASD) affects more than 1% of children in the United States, with the rate of new diagnoses climbing significantly in the last 15 years. Emergent conditions and subsequent visits to the emergency department (ED) can be particularly challenging for children with ASD, most of whom also have comorbidities in addition to their deficits in social communication and interaction. In the emergency setting, these conditions can cause a range of behaviors that result in challenges for health care providers and may result in suboptimal experiences for children with ASD and their families. We present the ED course of 3 children with ASD to illustrate these challenges, emphasize successful strategies, and highlight opportunities for improvement.